Influence of basin metals and novel wick-metal chips pad on the thermal performance of solar desalination process. (1st March 2020) - Sharshir, Swellam W.; Peng, Guilong; Elsheikh, Ammar H.; Eltawil, Mohamed A.; Elkadeem, M.R.; Dai, Hao; Zang, Jianfeng; Yang, Nuo
Abstract: In this study, efforts were made to enhance the performance of inclined wick solar still (IWSS) by integrating different basin metals and a novel wick-metal chips pad. Three different metal materials (aluminum, copper, and steel) were used as basin and their metal chips were sandwiched in a novel wick-metal pad. Experiments were carried out to figure out the influence of different basin metal materials and their metal chips filled in a wick pad on the thermal performance of IWSS. The enhanced solar still was compared with conventional inclined wick solar still (CIWSS). Results revealed that using aluminum and copper basins led to increase the productivity by 34.23% and 54.26%, respectively, compared with CIWSS. The use of metal chips sandwiched between two layers of wicks (wick-metal chips pad) caused an increase in the daily production by about 27.76%, 41.54, and 65.3% for steel, aluminum, and copper, respectively. This implies that the basin materials and the novel wick pads with metal chips, which acted as evaporation surface and heat storage medium, played a vital role in enhancing productivity. Also, the maximum thermal efficiency was 60.98% for the modified IWSS with copper basin and a novel wick-copper chips pad. While, the maximum thermal efficiency for the CIWSS with steel basin was 37%. To understand the temperature distribution through different layers of desalination surfaces, a numerical simulation was carried out under real weather conditions using the finite element software; COMSOL Multiphysics. Results showed that, there was a good agreement between experimental work and numerical investigation. Graphical abstract: Image 10485 Highlights: The proposed inclined wick solar still has thermal efficiency of 61%. Different combinations of basin metals and novel wick-metal chips pads were studied. Aluminum and copper basins lead to increase the productivity by 34% and 54%. Experimental results have been successfully verified by numerical simulation.